Controlling the spin–orbit branching fraction in molecular collisions - Heid, CG; Bentham, IP; Walpole, V; Jambrina, PG; Aoiz, FJ; Brouard, M (American Chemical Society, 2020)
The collision geometry, that is, the relative orientation of reactants before interaction, can have a large effect on how a collision or reaction proceeds. Certain geometries may prevent access to a given product channel, while others might enhance it. In this Letter, we demonstrate how the initial orientation of NO molecules relative to approaching Ar atoms determines the branching between the spin–orbit changing and the spin–orbit conserving rotational product channels. We use a recently developed quantum treatment to calculate differential and integral branching fractions, at any arbitrary orientation, from theoretical and experimental data points. Our results show that a substantial degree of control over the final spin–orbit state of the scattering products can be achieved by tuning the initial collision geometry.